Complete mitochondrial genome of Ptychobarbus kaznakovi (Teleostei: Cypriniformes: Cyprinidae), and repetitive sequences in the D-loop. (3rd May 2016) - Ma, Qingzhan; Wu, Bo; Li, Jiuxuan; Song, Zhaobin
Abstract: The complete mitochondrial DNA genome of Ptychobarbus kaznakovi was sequenced and characterized. The genome is 16, 842 bp in length. Similar with most teleosts, it has two ribosomal RNA (rRNA) genes, 13 protein-coding genes, 22 transfer RNA (tRNA) genes, and one displacement loop (D-loop) region. Conserved sequence blocks, including ETAS, CSB-B, D, E, F, and CSB1-3, were identified in the D-loop, which is similar to other species in Cypriniformes. Nevertheless, a 55 bp tandem repeat array was also identified at 3′ end of the D-loop, which is the first finding in Schizothoracinae. Phylogenetic analysis showed that the species of Ptychobarbus ( P. dipogon and P. kaznakovi ) formed a monophyletic group and represented close relationship to the species without scales in Schizothoracinae.